Dynamic Management Efficiency Evaluation of Education Service Industry and COVID-19 Pandemic Impact Analysis - Goh, Hyunwoo (International Journal of Membrane Science and Technology, 2023)
In Korea, the education service industry is always the subject of attention not only for its industrial aspect, but also for parents’ enthusiasm for their children’s education and the nation’s high enthusiasm for learning. In particular, during the COVID-19 pandemic, changes in the education service industry have had an impact on society as a whole. This study deals with changes in the management efficiency of Korea’s education service industry for 6 years and seeks to determine whether the COVID-19 pandemic has affected management efficiency changes. Therefore, from 2017 to 2022, the management efficiency of educational service companies is evaluated and analyzed. For this dynamic efficiency analysis, the DEA/Window technique was used, and the trend and stability of management efficiency were evaluated. Meanwhile, to analyze the difference in management efficiency between the time of the COVID-19 pandemic and before, a paired-samples t-test is conducted to determine statistical significance. It is expected that the management efficiency of educational service companies will be improved by utilizing the results of this study.